Kajian Kualitas Arsitektur Unity Menurut Elaraby (1978) di Masjid Raya Al-Mashun Kota Medan: Kajian mengenai kualitas arsitektur unity menurut Elaraby (1978) pada Masjid Raya Al-Mashun - Vever, Irza Wardani; Hasan, Soraya Masthura; Novianti, Yenni (Fakultas Teknik - Universitas Al Muslim - Bireuen Aceh- Indonesia, 2024)
Basically, the mosque is a place of worship for Muslims to fulfill their spiritual needs. In addition to spiritual needs, humans also need social needs as living beings as this has been regulated in the Al-Quran and Hadith. The mosque is also an important representative in Islamic architecture. Therefore, how can a mosque meet the architectural quality of unity, regardless of its main function? The purpose of this study is to examine how the unity of architectural quality according to Elaraby (1978) at the Al-Mashun Grand Mosque, Medan City. The method used in this research is descriptive qualitative method. The results of this study are regarding light-color and space-shape in related mosques which are important components of a unity in architectural design.